Subchronic Oral Exposure to Chlorpyrifos Decreases Butyrylcholinesterase in Wistar Rat - Sakinah, Elly Nurus; Supangat, Supangat; Wisudanti, Desie Dwi; Abrori, Cholis; Mustika, Arifa; Wibsono, Sony; Athoillah, Nabil (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Indonesia as an agricultural country has more than 33 million workers in the agriculture. Pesticides have an important role in agriculture because they function as powerful plant pest exterminators. However, its use is considered to cause various toxic effects, one of which is on the nervous system. This study aimed to evaluate the impact of pesticide exposure on cognitive impairment by assessing the butyrylcholinesterase biomarker in the blood of rats as experimental animals.Methods: This was a true experimental study conducted during September–November 2022 at the Pharmacology and Biochemistry Laboratory, Faculty of Medicine, University of Jember with a post-test only approach using Wistar rats which were divided into 1 control group and 4 treatment groups treated with chlorpyrifos 5 mg/kg orally. Serum butyrylcholinesterase enzyme levels were measured using the kinetic photometric method and then analyzed with a regression test in IBM SPSS® Statistics software.Results: The average value of butyrylcholinesterase was 920.23±145.27 (Control group); 904.48±91.6 (7 days after chlorpyrifos administration); 889.81±95.2 (14 days after chlorpyrifos administration); 457.84±69.5 (28 days after chlorpyrifos administration); 575.82±194.25 (56 days after chlorpyrifos administration). The results of the One-Way ANOVA test showed significant differences between groups as indicated by a significance test of 0.024 (p <0.05).Conclusions: There is a relationship between the duration of exposure to chlorpyrifos and butyrylcholinesterase levels in Wistar rats. This fact shows that the longer an organism is exposed to low doses of chlorpyrifos pesticides, the higher the level of neurological system toxicity that occurs in that organism.